Fraud by Abuse of Position and Unlicensed Gangmasters. Issue 2 (March 2016) - Collins, Jennifer
Abstract : This article analyses the Court of Appeal's interpretation of the fraud by abuse of position offence in R v Valujevs . Two issues are explored: first, the Court's welcome clarification of the meaning of a relevant 'expectation'; second, the inadequacy of the Court's reasoning in deciding that an unlicensed gangmaster 'is expected to safeguard, or not to act against, the financial interests' of his workers.